الرقابة القضائية على العملية الإنتخابية للمجالس المحليــة دراسة مقارنة بيـــن الجزائــر و تونس - مراد بن ساسي; بوبكر بوحوية (My University, 2022)
ABSTRACT The process of election of local councils in Algeria and Tunisia has established many shortcomings and criticisms because of the assignment of the supervision and control of the Department (executive branch) and this is making the legislator in both countries establish an independent body to be accompanied by all the stages of the election process In order to give transparency and to devote the required neutrality, while maintaining the judiciary as an independent control. This has clearly emerged through the election law in Algeria and Tunisia, nursing judges in various formations of committees supervising the electoral process, as well as the granting of the right to appeal as judicial to its various parties to the competent judicial bodies and is what is embodied Judicial. The judicial control is already embodied through texts for the electoral process, but the legislator remains prohibited for the pursuit of the elimination of the exercise of its control over the process of completely to remove the department in order to gain greater confidence in The competent authority oversees the elections, which are taking over to protect its voice until its free will be reflected in its representatives to achieve fair and transparent elections and therefore the democracy of the State ........................................ ملخص المذكرة : لقد شابت عملية إنتخاب أعضاء المجالس المحلية في كل من الجزائر وتونس العديد من أوجه القصور و الإنتقادات بسبب إسناد عملية الإشراف و الرقابة الى الإدارة السلطة التنفيذية) و هذا ماجعل المشرع في كلا البلدين ينشئ هيئة مستقلة تتكفل بكافة أطوار العملية الإنتخابية بغية إضفاء الشفافية اللآزمة و تكريس الحياد المطلوب ، مع الإبقاء على القضاء كجهة رقابة مستقلة . وبرز ذلك جلياً من خلال قانون الإنتخابات في الجزائر وتونس ، بإقحام القضاة في مختلف تشكيلات اللجان المشرفة على العملية الإنتخابية ضف الى ذلك منح حق الطعن الإداري كما القضائي لمختلف أطرافها أمام الجهات القضائية المختصة و هو ما يجسد الرقابة القضائية عليها. و إن كانت الرقابة القضائية مجسدة فعلاً من خلال النصوص المتعلقة بالعملية الإنتخابية إلا أن المشرع يبقى مدعواً للسعي أكثر لإقحام القضاء بممارسة رقابته على العملية كلياً في سبيل إبعاد الإدارة نهائياً عنها حتى يكتسب الناخب ثقةً أكبر في الجهة المختصة بالإشراف على الإنتخابات و التي تسهر على حماية صوته الى غاية تجسيد إرادته الحرة في إخيار ممثليه في سبيل تحقيق إنتخابات نزيهة وشفافة و بالتالي ديمقراطية الدولة.